Comparative Analysis of Different Efficient Machine Learning Methods for Fetal Health Classification - Alam, Md Takbir; Khan, Md Ashibul Islam; Dola, Nahian Nakiba; Tazin, Tahia; Khan, Mohammad Monirujjaman; Albraikan, Amani Abdulrahman; Almalki, Faris A. (Applied bionics and biomechanics, 2022)
Obstetricians often utilize cardiotocography (CTG) to assess a child’s physical health throughout pregnancy because it gives data on the fetal heartbeat and uterine contractions, which helps identify whether the fetus is pathologic or not. Obstetricians have traditionally analyzed CTG data artificially, which takes time and is unreliable. As a result, creating a fetal health classification model is essential, as it may save not only time but also medical resources in the diagnosis process. Machine learning (ML) is currently extensively used in fields such as biology and medicine to address a variety of issues, due to its fast advancement. This research covers the findings and analyses of multiple machine learning models for fetal health classification. The method was developed using the open-access cardiotocography dataset. Although the dataset is modest, it contains some noteworthy values. The data was examined and used in a variety of ML models. For classification, random forest (RF), logistic regression, decision tree (DT), support vector classifier, voting classifier, and K-nearest neighbor were utilized. When the results are compared, it is discovered that the random forest model produces the best results. It achieves 97.51% accuracy, which is better than the previous method reported.